Calycosin ameliorates albuminuria in nephrotic syndrome by targeting Notch1/Snail pathway - Xiaohong Ma; Binghe Guan; Linrong Pang (BMC Nephrology)
Abstract Background Heavy proteinuria is an important hallmark for kidney disease including nephrotic syndrome. Astragali Radix, a traditional Chinese herb, holds the potential to alleviate nephrotic syndrome; however, the underlying mechanism has not been completely clarified. The study aimed to explore the role of calycosin (C16H12O5), a major active component of Astragali Radix, in regulating adriamycin-induced proteinuria. Methods A rat model of nephrotic syndrome was established through two adriamycin injections within two weeks (4 mg/kg for the first week and 2 mg/kg for the second week). After the induction of renal injury, 10 mg/kg or 20 mg/kg calycosin was intraperitoneally injected into rats for four weeks. Before euthanasia of rats, urine and blood samples were collected, and body weight was recorded. Then, 24 h urine protein content, kidney index, total cholesterol (TC), triglyceride (TG), as well as renal function indicators including blood urea nitrogen (BUN), serum creatinine (SCR), and urine albumin excretory rate (UAE) were measured. Hematoxylin-eosin staining for renal cortex tissues was performed to evaluate glomerular structural damage. TUNEL assay was performed to evaluate renal cell apoptosis. Western blotting was conducted to measure protein levels of podocyte-specific markers (podocin and nephrin), Notch1, and Snail in rat renal tissues. Results Calycosin reversed adriamycin-induced increase in proteinuria content, kidney index, and concentrations of renal function indicators. Calycosin ameliorated glomerular structural damage, inflammatory cell infiltration, and basement membrane thickening in model rats. In addition, calycosin rescued the suppressive impact of adriamycin on renal cell apoptosis and protein levels of podocyte markers. The activated Notch1/Snail signaling in model rats was suppressed by calycosin intervention. Conclusion Calycosin exerts a protective role against adriamycin-induced nephrotic syndrome via inhibition of the Notch1/Snail signaling. Clinical trial details Not applicable.